Variação das vogais médias em posição pretônica nas regiões norte e sul de Minas Gerais : uma abordagem à Luz da Teoria da Otimalidade - Rubens Vinicius Martins Guimaraes (2007)
The current dissertation presents an analysis concerning the behaviour of the medium vowels, in pre-stress position, based on the data obtained from the dialects of the areas South and North of the State of Minas Gerais. In such areas, an interesting phenomenon is produced, which is basically summarized in the following aspects: in the South area, the presence of the mid-low vowel in position pretonic is not observed in the speakers production, while the presence of that vowel in certain phonological contexts is quite relevant in the North area. Besides the variation inter-dialectal, it was also verified the intra-dialectal variation brought into pratice in the South as well as in the North area. The different variations, the processes and phonological atmospheres wich act determining the speakers' choices were described properly and analyzed based on the Optimality Theory. As from an input always constituted of mid-high vowel, it was noticed that, in the South area, the constraints which show themselves active are IDENT [ATR], IDENT (HEIGHT) and *MID. In that dialect, the constraints IDENT [ATR] and IDENT (HEIGHT) are responsible for the preservation of the structure of the input, while the constraint *MID acts determining the vocalic reduction and, consequently, the lifting of the mid-high vowel. Besides the constraints already mentioned and their respective functions, the AGREE and *e/o show themselves active in the North area. The first acts determining that the mid-high vowel becomes mid-low vowel based on the process of vocalic harmony. AGREE foresees that, if the tonic vowel on the input were mid-low, the feature [-ATR] should be assimilated by the medium vowel in position pretonic defining the changing. On its turn, the constraint *e/o reveals the neutralization in position pretonic of the mid-high vowels, turning them into mid-low. All of the processes were approached from the classical version of the Optimality Theory and the variacionistas proposals of Anttila & Cho (1998) and Coetzee (2005). At the end, it still presented a possible approach from Lee & Oliveiras (2006).